2022
DOI: 10.1136/bmjpo-2021-001308
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related occupational stress in staff in an acute paediatric teaching hospital in Ireland

Abstract: BackgroundThe COVID-19 pandemic has resulted in major strains for healthcare staff.ObjectivesThis study aims to assess prevalence of occupational burnout (BO) during COVID-19 in staff working in an acute paediatric hospital setting.ParticipantsOne hundred and thirty-three staff, out of 1900 eligible staff (9.6% response rate), completed an online or paper and pencil survey.MethodsThe Copenhagen Burnout Inventory was used as the main outcome measure. Additional questions examined the impact of COVID-19 and rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
1
9
0
1
Order By: Relevance
“…Efforts to reduce the spread of the virus, such as lockdowns, the migration to virtual healthcare consultations, the cancellation of elective care, and visitor restrictions, all impacted normal healthcare delivery [1,3]. Healthcare staff experienced immense pressure during the early stages of the pandemic, with limited initial knowledge about the features of the virus or its transmission, a shortage of appropriate personal protective equipment (PPE), and the psychological strain of treating patients who were very sick with COVID-19 [4][5][6][7]. Two years on from the beginning of the pandemic, the true extent of the impact the virus has had on the safety and quality of care provided to patients is beginning to be understood [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to reduce the spread of the virus, such as lockdowns, the migration to virtual healthcare consultations, the cancellation of elective care, and visitor restrictions, all impacted normal healthcare delivery [1,3]. Healthcare staff experienced immense pressure during the early stages of the pandemic, with limited initial knowledge about the features of the virus or its transmission, a shortage of appropriate personal protective equipment (PPE), and the psychological strain of treating patients who were very sick with COVID-19 [4][5][6][7]. Two years on from the beginning of the pandemic, the true extent of the impact the virus has had on the safety and quality of care provided to patients is beginning to be understood [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown similar results across different settings and disciplines. 6,26 However, not all studies have found this difference between genders. It was assumed that burnout is a female experience, 27 but burnout may be experienced differently by men and women.…”
Section: Covid-19-related Factorsmentioning
confidence: 98%
“…In our study, COVID-19-related variables, such as access to PPE or information about COVID-19, did not have a significant effect on burnout, which is at odds with previous studies. 6,9 This might be accounted for by the timing of our study (conducted toward the end of the second wave of the COVID-19 pandemic, where many of these issues, including uncertainty, had been resolved) and/or of the location of the study (conducted in a community setting as opposed to the hospital setting where access to such protective wear is of greater importance). Intention to change job and higher time spent outside primary responsibilities were independent predictors of personal and workrelated burnout.…”
Section: Covid-19-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, many hospital staff feel they have been busier and more stressed than ever before. 5,6 When things go wrong in hospital, as they inevitably will from time to time, staff should realise that parents' anger is in part an attempt to regain control, and should try not to be perturbed by it, that is, exercise self-control. While parents' anger may be understandable, however, limits should be placed when such anger manifests as rudeness to staff.…”
mentioning
confidence: 99%